New Countries are Applying the Harmonized System Nomenclature – Update 2012 - Carsten Weerth (Global Trade and Customs Journal, 2012)
More and more countries and economic regions are applying the Harmonized Commodity Description and Coding System (Harmonized System Convention). This paper examines in the update 2012 the new countries which are using the worldwide uniform language of trade.
Additional information: Pre-Print Proofs, according to ROMEO/Sherpa-policy of this yellow policy journal.
Keywords: F53; K33; K34; 330; Customs Law; Harmonized System; World Customs Organization; Customs Classification; Tariff Classification; Trade Facilitation